Nurses' and Midwives' Knowledge Toward Postpartum Hemorrhage Prevention in Kerbala City, Iraq - Hadeel Rasheed Seger, Ph.D (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Postpartum hemorrhage remains a major obstetric emergency and a leading contributor to maternal morbidity and mortality worldwide, requiring competent health professionals capable of recognizing and preventing the condition during maternity care. Specific Background: Nurses and midwives play a central role in maternity services, particularly in identifying risk factors, applying preventive measures, and implementing clinical protocols related to postpartum hemorrhage prevention in hospital settings. Knowledge Gap: Despite established clinical guidelines and international recommendations, evidence indicates that knowledge among healthcare providers may vary, and limited data exist regarding the level of understanding among nurses and midwives working in maternity facilities in Kerbala City, Iraq. Aims: This study aims to assess the knowledge of female nurses and midwives regarding postpartum hemorrhage prevention and to determine the association between knowledge levels and selected sociodemographic variables. Results: A descriptive cross-sectional study involving 60 participants revealed that 53.3% demonstrated poor knowledge scores, while 46.7% achieved good scores. Statistical analysis indicated no significant association between knowledge levels and age, educational level, years of working in the delivery room, participation in postpartum hemorrhage courses or workshops, or current workplace within the hospital. Novelty: The study provides recent empirical evidence describing the knowledge profile of maternity healthcare staff in a teaching hospital in Kerbala City, highlighting areas of insufficient understanding in postpartum hemorrhage prevention. Implications: The findings emphasize the necessity of structured training programs, continuous professional education, and regular knowledge assessment to strengthen clinical preparedness of nurses and midwives in maternity care and support safer maternal health services. Highlights:• Majority of Participants Demonstrated Insufficient Understanding of Preventive Measures Related to Obstetric Bleeding Emergencies.• Statistical Testing Showed No Relationship Between Knowledge Scores and Demographic or Professional Characteristics.• Findings Indicate the Need for Structured Professional Education and Continuous Assessment in Maternity Services. Keywords: Postpartum Hemorrhage Prevention, Nurses And Midwives Knowledge, Maternal Health Care, Obstetric Emergency Management, Iraq